Pengaruh Lingkungan Kerja dan Motivasi Terhadap Kepuasan Kerja dan Dampaknya Terhadap Kinerja Pegawai pada Kantor Pertanahan Kabupaten Merangin Provinsi Jambi - Kartono Agustiyanto; Tety Asnawi; Susilawati Susilawati (Universitas Batanghari, 2019)
The purpose of this research are to knowing, analyze, and reviewing the influence of work environment and motivation on job satisfaction and impact on employee performance at Land Office, Regency of Merangin, Jambi Province. The analysis method used are descriptive analysis and verification analysis. Descriptive analysis is used to reveal the facts of the object that have been research. While verification analysis is used to test and measure the influence of independent variable X1 (Work Environment) and X2 (Motivation) to the dependent variable Z (Performance) with intervening variable Y (Job Satisfaction). The result of this research and hypothesis testing that have been conducted got the result that : 1) Effect of work environment on job satisfaction directly and indirectly is 9,001%; 2) The influence of motivation on job satisfaction directly and indirectly is 69,739%; 3) Effect of work environment and joint motivation to job satisfaction is 78,740%; 4) The effect of working environment on the performance directly and indirectly is -1,945 %; 5) The influence of motivation on performance directly and indirectly is 15,639%; 6) The influence of working environment and joint motivation on performamce is 13,693%; 7) The effect of job satisfaction on performance is 15,682%; 8) The influence of working environment and joint motivation on performance through job satisfaction is 14,009%.